Aesthetic Management of Coronal Dilacerations with Enamel Hypoplasia of Permanent Maxillary Central Incisors: - Nehal Amir; Muqadus Hayat (Journal of Bahria University Medical and Dental College, 2025)
Dilaceration is a peculiar developmental dental anomaly. It is associated with traumatic events of deciduous teeth affecting the permanent tooth buds. It is chiefly a precipitous change in the axial inclination between the crown and the root of a tooth. Dilacerated crown, a rare clinical presentation, is a result of the non-axial displacement of pre-formed hard tissues of a developing crown at an angle to its longitudinal axis. It conspicuously impacts the appearance of patient. Enamel hypoplasia is primarily due to the trauma or infection of primary predecessor tooth resulting in a quantitative defect in enamel of permanent successors. Occasionally, both conditions; dilacerated crown and enamel hypoplasia can occur concomitantly producing many unpropitious outcomes. This particular case is about a 14-year-old boy presenting to the Department of Operative dentistry and Endodontics for the esthetic management of anomalous maxillary central incisors. These anomalous teeth were conservatively managed using direct composite veneers.